The Waqf System and Its Role in Economic Development (El-Wahat Journal for Research and Studies, 2026)
The waqf system plays a fundamental and vital role in achieving sustainable economic development by serving as a financial and investment tool that combines saving and investing to provide permanent financial and in-kind resources supporting various vital economic sectors, such as agriculture, industry, trade, and services. Waqf contributes to mobilizing idle funds and transforming them into ongoing development projects that enhance productivity and expand the investment base, while also strengthening the social and economic infrastructure that supports comprehensive development. Additionally, waqf alleviates financial pressures on the state by funding many social and service projects and provides continuous support to the poor and needy, thereby reinforcing social solidarity and promoting economic and social stability. From this perspective, waqf is considered an important economic pillar that contributes to achieving sustainable development aimed at the welfare of the entire society and ensuring continuous and balanced economic growth.